Space use by Rhabdosargus holubi in a southern African estuary, with emphasis on fish movements and ecosystem connectivity. Issue 2 (3rd April 2017) - Grant, GN; Cowley, PD; Bennett, RH; Murray, TS; Whitfield, AK
Abstract : Twenty-one juvenile Cape stumpnose Rhabdosargus holubi (140–190 mm fork length) were tagged with internal acoustic transmitters in the lower, middle and upper reaches of the Kowie Estuary, South Africa. The movements of each fish were continually monitored from October 2014 to February 2015 using 22 stationary data-logging acoustic receivers situated at approximately equidistant intervals along the length of the estuary (21 km). Juvenile R. holubi spent the greatest proportion of time within the estuarine environment (83%), with the sea (16%) and riverine (1%) environments used to a much lesser extent. Within the estuarine environment, tagged individuals showed high levels of residency and fidelity to their capture and release sites; however, the degree of residency was dependent on the position of the release site, with batches in the upper and lower reaches exhibiting different space-use patterns. When larger juvenile R. holubi migrated back to the sea for the next phase of their life cycle, they generally did not return to the estuarine environment, thus indicating a permanent ontogenetic shift in habitat use with the onset of sexual maturity. This contribution to our understanding of the ecology of a ubiquitous estuarine fish further highlights the importance of estuarine habitats as nursery areas that require effective management.